Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
First, we substitute the x value into the equation below, which is essentially saying
y = 2(10) - 6
We multiply and get
y = 20 - 6
Subtract, and get a final answer of
y = 14
x = 10
y = 14
So the answer is (10, 14)
Hope this helps!
y = 2(10) - 6
We multiply and get
y = 20 - 6
Subtract, and get a final answer of
y = 14
x = 10
y = 14
So the answer is (10, 14)
Hope this helps!
Answer:
(10, 14)
Step-by-step explanation:
Hello there!
Given such a problem, we have been told to use substitution method to solve it.
To cut it short, substitution refers to replacing a variable with a value.
Here is a way to solve this problem even in future:
- simplify the equation given
- solve the equation for the variable x or y
- substitute as step 2 above for the other variable
- solve the newly obtained equation
- and finally solve the equation to find the value of variable not yet obtained.
Back to our problem,
y = 2x - 6, x = 10
Substitute x into equation y = 2x - 6
y = 2(10) - 6
= 20 - 6
= 14
. ° . x = 10, y = 14
Variables in terms of x and y
(x, y) = (10,14) ✓
This is our answer.
I hope this helps.
Have a nice studies.
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.